2020
DOI: 10.1007/s00432-020-03221-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of prostate cancer in Middle Eastern population highlights differences with Western populations with prognostic implication

Abstract: Background To investigate the incidence and prognostication of ERG, PTEN and SPINK1 protein expressions in prostate cancer cohort of Middle Eastern descent in comparison to published data from Western populationMethods Immunohistochemistry for ERG, PTEN and SPINK1 was performed in cohort of localized PCa (n=340). Data correlated to pathological and clinical outcomes and compared to Western populations.Results ERG expression and PTEN loss noted in 123/288 (42.7%) and 91/297 (30.6%) of patients, respectively. SP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Increased prevalence was observed in western countries (54%) as compared to Asian countries (23%) 2 . Study conducted by Abdelsalam et al, demonstrated 42.7% ERG positive prostate tumor in their cohort 15 . Forty nine percent incidence was documented by verdu et al 16 .…”
Section: Prostatic Adenocarcinoma Is Second Most Common Malignancy Worldwide Particularly In Europeanmentioning
confidence: 78%
“…Increased prevalence was observed in western countries (54%) as compared to Asian countries (23%) 2 . Study conducted by Abdelsalam et al, demonstrated 42.7% ERG positive prostate tumor in their cohort 15 . Forty nine percent incidence was documented by verdu et al 16 .…”
Section: Prostatic Adenocarcinoma Is Second Most Common Malignancy Worldwide Particularly In Europeanmentioning
confidence: 78%
“…Most of our patients achieved good response of ADT, so changing the therapy protocol or adding a new agent were not necessary. These findings do emphasis on the variations in progression and prognostication of PCa; therefore, validation of western therapeutic protocols for the managements of PCa is recommend for other nations and societies [4].…”
Section: Discussionmentioning
confidence: 97%
“…In the USA alone, there will be an estimated 191,000 cases of PCa diagnosed in the year 2020 of which approximately 20% will be metastatic [3]. In the Middle Eastern population, there are variations in PCa incidence, progression, and prognostication compared to the Western population which may be due to significant difference in key molecular events [4]. African-American men have a higher risk of lethal PCa compared to European-American men [5].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we investigated the significance and incidence of key genetic alterations related to ERG , PTEN, and SPINK1 in a different Middle Eastern cohort relative to a different European cohort [ 9 ]. The study documented that ERG , PTEN, and SPINK1 genomic alterations occurred less frequently in the Middle Eastern cohort and that an enrichment of ERG and PTEN loss was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, several somatic genomic alterations differ in frequency between ancestries, including TMPRSS2-ERG genomic rearrangements, SPINK1 overexpression, and SPOP single nucleotide variants (SNVs), supporting differences in prostate cancer risk and pathway progression [ 7 , 8 ]. The rate of PTEN loss, as assessed by IHC, is lower in men of ME ethnicity, and tumors with PTEN loss are not enriched for ERG loss, as documented in EUR cohorts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%